Amazonian Community Discourses on the Human-Nature Relationship (Andamios, Revista de Investigación Social, 2025)
In the context of the global ecological crisis, this article analyzes the human–nature relationship in Amazonian communities, using the Awajún community of Wawas in the Peruvian Amazon as a case study. Employing a qualitative approach, an ethnographic design was developed to evaluate the forms of human–nature interaction in the community, identifying four categories that distinguish discourses of compatibility, separation, incompatibility, and combination. The findings highlight the predominance of the discourse of compatibility, which frames the human–nature bond from a collective and integrative perspective, moving away from traditional dualism. This research contributes to the understanding of community-based knowledge and its role in sustainability and epistemic resistance to capitalist logics.
Keywords: Human–nature relationship; peruvian amazon; discourse analysis; ethnographic study; sustainability